Supply, installation, commissioning and post implementation support of IP phone solution with manufacturer's 03 years warranty for Brac University new campus building at holding no. Kha 224, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Technometrics Limited to supply, installation, commissioning and post implementation support of IP phone solution for Brac University new campus project.